Comparative Analysis of Himawari-8 Satellite Monitoring and Early Warning Characteristics in Short-Time Heavy Precipitation Weather over Qinghai Plateau - Ping ZHU; Jianshe XIAO (Gaoyuan qixiang)
In order to obtain the heavy precipitation monitoring and early warning characteristics and early warning methods of convective clouds over Qinghai Plateau （hereinafter referred to as plateau）， the Himawari-8 satellite datum in typical heavy precipitation weather processes over the plateau were used to track and identify convective clouds， the clouds characteristic parameters with early warning significance were calculated and analyzed.The results show that： （1） An improved multi-channel method for convective clouds identification was proposed in this paper， Compared with the traditional multi-channel method， it was proved that the obtained clouds were closer to the convective main body， and was suitable for convective clouds identification over the plateau.（2） From convection formation to maturity， the characteristic parameters fluctuated， but the minimum brightness temperature difference between infrared channel 1 and water vapor channel （DTB13） and the minimum brightness temperature （Tmin） of cloud top decreased as a whole， and the maximum brightness temperature gradient （GTmax） of cloud top increased as a whole.In the convective development stage， only the minimum brightness temperature difference between infrared channels 1 and 2 （DTB12） reached the early warning extreme value on average.And in the mature stage， it reached the early warning extreme value on average， such as Tmin， DTB13， GTmax and deep convection index （DCI）.Convective clouds in heavy precipitation weather over the plateau mostly developed into deep convection， and precipitation occured near the extreme value of characteristic parameters of clouds， and the short-time heavy precipitation occured in the extreme value area or near the edge of the characteristic parameters of the specific cloud tops （upwelling cloud tops or approximate upwelling cloud tops） in the deep convective cloud area.（3） The extreme values of characteristic parameters appeared 0~1 h and 0.5~4.5 h ahead of the start time of general precipitation and heavy precipitation respectively， and its advance time to the heavy precipitation beginning was relatively the earliest in the westerly flow field type.Before the precipitation beginning， the change of convective clouds developed towards deep convection was the most intense under the subtropical high pressure type flow field， which showed that the average DCI and the mean GTmax were the largest respectively， and the average DTB12 was the smallest， while the cumulus development under the westerly flow field was relatively weak.After the beginning of precipitation， the deep convection in the westerly flow field was relatively shallow， but the change of cloud top was still intense， which showed that the mean DCI and mean Tmin were lower respectively， but the mean GTmax and average DTB13 were larger respectively， and the convection development in the low vortex shear flow field was relatively deepest.（4） The early warning method for short-time heavy precipitation over the plateau was proposed in this article as follows： when the convective clouds developed into the specific cloud top， within the 50km range centered on the geometric center of the specific cloud top， if Tmin≤223 K， DCI≥20 K， GTmax≥18 K， DTB12≤0 K， DTB13≤3 K were met at the same time， then， which indicated that the short-time heavy precipitation would come or continue under the specific clouds area.It was verified that this method has high practical value in the short-time heavy precipitation early warning of deep convective clouds over the plateau.